2020
DOI: 10.1007/s13197-020-04430-5
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of solutions involving organic acids in the extraction of the anthocyanins present in jabuticaba skins (Myrciaria cauliflora) and red cabbage leaves (Brassica oleracea)

Abstract: Anthocyanins make up the largest group of water-soluble pigments of the vegetable kingdom. These bio-compounds with antioxidant properties are attracting great interest in the food, pharmaceutical and cosmetic industry mainly because of their presence in many fruits and vegetables. The extraction of the pigment is still in need of further studies, especially concerning the extraction yield and the use of friendly solvents. The use of acidulants has shown an alternative to improve the extraction. This work pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The effect of the volume fractions of ethanol of 100%, 80%, 60%, and 40% on the yield of anthocyanins is shown in Figure S2B. The total content of anthocyanins increased with the ethanol content rising from 40% to 80%, because organic solvents might promote the cell membrane denaturation and the release of anthocyanins . However, the content decreased when the ethanol content was 100% in that the solvent extracting hydrophilic anthocyanins must contain a small amount of water .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the volume fractions of ethanol of 100%, 80%, 60%, and 40% on the yield of anthocyanins is shown in Figure S2B. The total content of anthocyanins increased with the ethanol content rising from 40% to 80%, because organic solvents might promote the cell membrane denaturation and the release of anthocyanins . However, the content decreased when the ethanol content was 100% in that the solvent extracting hydrophilic anthocyanins must contain a small amount of water .…”
Section: Resultsmentioning
confidence: 99%
“…The total content of anthocyanins increased with the ethanol content rising from 40% to 80%, because organic solvents might promote the cell membrane denaturation and the release of anthocyanins. 29 However, the content decreased when the ethanol content was 100% in that the solvent extracting hydrophilic anthocyanins must contain a small amount of water. 30 Hence, the volume fraction of ethanol was set at 80%.…”
Section: Optimization Of Uae Conditions 311 Effect Of One-factor Expe...mentioning
confidence: 99%
“…Musso et al observed that when the extract with water ethanol was stirred for half an hour at 300 rpm, the anthocyanin contents found in the alcoholic and aqueous extracts were 4 and 0.6 mg/L, respectively ( 107 ). Galvao et al also observed that in a magnetic stirred batch with water, methanol, isopropanol, and ethanol at a controlled temperature of 25 C for a period of 3 h, the anthocyanin contents were found to be 50.37, 19.44, 0.77, and 0.76 mg/ L, respectively ( 108 ). Stirring in an orbital shaker with acidified water (0.05 M H 3 PO 4 ) at 90 rpm for 12 h, the anthocyanin concentration was 32.05 mg/L ( 109 ).…”
Section: Extraction Technology Of Anthocyaninsmentioning
confidence: 99%